Descriptive imagenological aspects of osteoma in the jaws: Review of the literature. - Angulo-Díaz, Carlos Manuel (2020)
Osteomas are benign osteogenic lesions derived from compact or spongy bone. They are characterized by their slow growth and appear more frequently between 20 and 50 years of age, with a higher prevalence in men than in women. These lesions are clinically asymptomatic and canbe found in the craniofacial region, particularly in the paranasal sinuses and the mandible, and may have a central, peripheral or extraosseous presentation. Multiple osteomas are related to Gardner's Syndrome. Treatment of osteoma is surgical when complications develop. Imaging studies such as panoramic radiography and cone beam computed tomography are the modalities most widely used to determine the location, extent, and anatomical relationships of the lesion. Imaging features may present as a bony excretion of compact, spongy, or mixed bone. Adequate knowledge of these lesions allows adequate diagnosis and better treatment planning.